Subcutaneous emphysema in oral surgery procedure: Review of literature. - Cabanillas Taco, Elías Alejandro (2019)
Objective: Determine the most frequent cause of subcutaneous emphysema in oral surgery, as well as risk factors, diagnosis and treatment. Material and methods: Comprehensive literature search through PubMed & Cochrane from 2009 to 2018. Surgical procedures reports were used. Cases caused by trauma and root canals were excluded. We found 21 reports that met our inclusion criteria. Results: It was found that 14 of the 21 cases were related to the use of high-speed handpiece. Other cases included: 4 for the use of the Air Syringe and 3 for patient activities after the surgical procedure. Conclusions: Subcutaneous emphysema can have serious and life-threatening effects if not treated properly. Special care must be taken with the use of high-speed handpieces. Clear instructions should be given to patients after surgical procedures.